Practical Ruby projects : ideas for the eclectic programmer - Cyll, Topher (Springer, 2017)
Want to take Ruby to the limit? Looking for new, powerful, and creative ideas that will take Ruby beyond Rails and web programming? If you're comfortable with Ruby, you'll be itching to go further—apply Practical Ruby Projects: Ideas for the Eclectic Programmer and become a master of advanced Ruby techniques.